Aplikasi Metode Sequencing Pada Jasa Service Kamera Digital Studi Kasus di MOR â C Photography Bandung - Camelia, Ayu Fitri (Business Administration Study Program - Universitas Katolik Parahyangan, 2016)
MOR â C photography is a company that offer services for digital camera and lens be based order by customer, the production process used sequence method to avoid lateness in service order. The author is using description method in research method. The research is doing by case study in production process of service company, and then identification various of factor that influence production process. The technique to collected actual data from the service company, the author used interview, observation, and documentary data from company.In sequencing method there are many method used by companies in general like FCFS (First Come, First Serve), SPT (Short Processing Time), LPT (Longest Processing Time), EDD (Earlier Due Date), and CR (Critical Ratio). MOR â C photography used FCFS method in sequence of service order, but still occured lateness in order first week 12,8 days; second week 11,8 days; third week 17,9 days; and fourth week 13,1 days. MOR â C photography should use SPT method to finished the order be based short processing time and routine controling total of order. SPT method will be more effective with batch system, is system that collected amount of order be based short processing time and then processing them.Â Keywords : Sequence Method; FCFS (First Come, First Serve); SPT (Short Processing Time); LPT (Longest Processing Time); EDD (Earlier Due Date); CR (Critical Ratio)